Self-Serving Biases in Bargaining. Explaining Impasse - Simone Kohnz (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
There is strong evidence that in bargaining situations with asymmetric outside options people exhibit self-serving biases concerning their fairness judgements. Moreover, psychological literature suggests that this can be a driving force of bargaining impasse. This paper extends the notion of inequity aversion to incorporate self-serving biases due to asymmetric outside options and analyses whether this leads to bargaining breakdown. I distinguish between sophisticated and naive agents, that is, those agents who understand their bias and those who do not. I find that breakdown in ultimatum bargaining results from naiveté of the proposers.
urn:nbn:de:bvb:19-epub-899-2
Keywords: A13; C7; D63; 330; fairness perceptions; self-serving bias; inequity aversion; ultimatum bargaining; outside options